KONSISTENSI STRATEGI PEMASARAN DALAM MENDUKUNG PENCIPTAAN BISNIS UMKM BERKELANJUTAN - Ristanti, Ristanti; Sulistyo, Agung (Juremi: Jurnal Riset Ekonomi, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in the development and growth of the Indonesian economy. Several areas, such as empowering the community's economy, opening up job opportunities, and helping government programs, are the impacts of the presence of MSMEs. The increasing development of MSMEs has ultimately given rise to competitive competition. Businesses can implement many strategies to create sustainability, one of which is through the implementation of the marketing mix. This study is essential to see how business actors carry out the implementation of the marketing mix strategy. This study will provide an overview of how businesses implement their strategies. Data collection uses questionnaires and contains the implementation of the marketing mix. A purposive sampling-based sampling technique was used in this study. A sample of 150 was selected from micro and small businesses in the Special Region of Yogyakarta (DIY) that met the requirements. This study's data analysis stages include data transcription, data reduction, coding and categorization, and drawing conclusions. Interviews with product users (consumers) were also conducted in this study to maintain data quality. Based on the analysis results, most business owners generally understand and apply the concept of the 4p marketing mix. The critical role of marketing is to provide businesses with guidance and perspective in meeting the needs of their consumers.